Compound chenpi tea consumption reduces obesity‐related metabolic disorders by modulating gut microbiota and serum metabolites in mice - Wang, Jianwei; Hao, Jinhua; Miao, Danyang; Xiao, Pingting; Jiang, Xiaoyu; E‐Hu, Liu (Journal of the science of food and agriculture, 2024)
BACKGROUNDCompound chenpi tea (CCT) is a popular herbal beverage made from citri reticulatae pericarpium, Ganoderma lucidum, and pu‐erh tea. This study aimed to investigate the anti‐obesity effect of CCT in mice fed a high‐fat diet (HFD) and to explore the potential mediators by 16S ribosomal RNA sequencing and serum metabolomic analysis.RESULTSThe results showed that CCT supplementation can effectively reduce diet‐induced obesity, hepatic steatosis, dyslipidemia, and insulin resistance. Further analyses revealed that CCT could reverse the changes of 28 metabolites induced by HFD, mainly affecting, amino acid metabolism, gut microbiota metabolism, and glycerophospholipid metabolism. CCT could also alleviate the intestinal dysbiosis by decreasing the abundance of Romboutsia, Gemella, [Eubacterium]_fissicatena_group, and Faecalibaculum, and increasing the abundance of Oscillibacter, Blautia, and Acetatifactor.CONCLUSIONCollectively, these findings demonstrated that CCT supplementation modulated gut microbiota and obesity‐related metabolic disorders in mice. © 2023 Society of Chemical Industry.